Practice of Embryo Transfer: Recommendations During and After - ÖZCAN, PINAR; Tiras, Bulent; Cenksoy, PINAR (My University, 2014)
Many patient and embryo factors influence the outcome of assisted reproductive technology (ART) treatment. The predictors for a successful ART cycle include female age, ovarian reserve, embryo quality, endometrial receptivity, and embryo transfer (ET) technique. ET, the final step of ART, has recently been noted as a crucial step affecting ART success. Variables affecting pregnancy rates following ET include ultrasound guidance, ease of ET transfer, catheter type, transfer and catheter-loading technique, blood or mucus effects, retained embryos, trial transfer, the physician-s experience, and catheter tip placement. Despite the lack of consensus regarding the optimal ET technique, it is generally recommended that during ET, the disruption of the endometrium and the induction of uterine contractions should be avoided. The exposure of embryos to the ambient conditions should be minimized, and the embryo(s) should be placed at an optimal position within the fundal region of the uterine cavity.